Global security - a sourcebook: volume 5 ; Africa - Echtler, Magnus; Burchardt, Marian (De Gruyter, 2025)
This volume explores secularity in Sub-Saharan Africa, an area long considered to be, to quote John Mbiti, “notoriously religious”, or lurking in the secular shadows. Our sources question these assumptions by showing how contemporary secularities in Africa emerged from specific socio-cultural histories, and political conflicts and contestations, as well as from colonial impositions and African interventions. Organised thematically, the volume begins by showing how the constitutions of African post-colonial states regulate religion, with introductions providing the historical and political contexts of the specific configurations. The next sections deal with religionisation and culturalisation – the basic processes of dealing with the African past, and of reading African indigenous concepts, vocabularies, practices, and symbols, within the framework of religious-secular distinctions. We present sources debating the separation of religion and politics from African socialism, atheist organisations, and public debates. Two further sections deal with expressions of secularity in African literature and photography. The last three sections share a regional focus on southern Africa, but tell rather different stories about the colonial formation and subsequent transformations of secularity